Study on the evolution of oxygenated structures in low-temperature coal tar during the preparation of needle coke by co-carbonization. (1st January 2022) - Zhang, Zhichen; Huang, Xiaoqiao; Zhang, Lanjie; Guo, Shuhai; Du, Hui; Chen, Zhaojun; Wu, Bo; Li, Gang; Liu, Dong
Highlights: Enriching the aromatics was conducive to weaken the effect of phenolics. The addition of aromatics dispersed oxygen-containing cross-linked structures. C–OH/C–O/C–O–C was first converted to COO– then to CO during carbonization. Abstract: Low-temperature coal tar is rich in oxygenated compounds which are hard to remove and make a great influence on the quality of needle coke. Low-temperature coal tar (LTCT) and decant oil (DO) were used to co-carbonize to prepare needle coke by liquid phase carbonization, and the evolution of oxygenated structures in LTCT during the preparation of needle coke was investigated. In the early stage of carbonization process, the C–OH/C–O/C–O–C functional groups were mainly transformed into COO– groups. With the deepening of carbonization depth, the COO– functional groups gradually converted into CO functional groups. The enrichment of aromatics and the introduction of high aromaticity material further promoted the conversion of oxygenated structures and the oxygen-containing crosslinking behavior. Excessive aromatic molecules provided active sites and free radicals for polycondensation and dispersed the distribution of oxygenated cross-linked structures in the whole carbonaceous structures, thus resulting into a more ordered lamellar orientation. This study provided theoretical basis for weakening the influence of the oxygenated structures on the quality of needle coke by enhancing aromatic content during co-carbonization.